Study of total cellulose, phenol and tannin content in ethanol extract of orange and pomegranate peel by using sonication - RAJA N. E; CHANDRA MOHAN C; SUJA D; MEENA K (International Journal of Pharma and Bio Sciences, 2019)
The orange fruit belongs to Citrus species. The botanical name is Citrus sinensis, belonging to family Rutaceae. This fruits are sweet in nature and citrus aurantium is considered to be bitter in taste than the other varieties. The citrus peel are rich in nutrients and contain many phytochemicals which can also be used efficiently as drugs and food supplements. Pomegranate is considered to be one of the oldest known edible fruits. Pomegranate peels are characterized by an interior network of membranes comprising almost 26–30% of total fruit weight and are characterized by substantial amounts of phenolic compounds, including flavonoids and tannins. Recycling of fruit waste is one of the most essential needs for utilizing it in a number of innovative ways yielding new products and meeting the requirements of essential products required in human, animal and plant nutrition as well as in the pharmaceutical industry. The purpose of the present study was to evaluate the effect of using different temperatures with ethanol extract in orange and pomegranate peel. Phytochemical screening was carried out with standard procedures of ethanol solvent in orange and pomegranate peel extracted by using ultra sonicator at various temperatures (37ºc and 50ºc) to evaluate the presence of phytochemicals such as Phenol, cellulose and tannins. The peel samples show the strong presence of Cellulose, Tannins, and Phenols in ethanol extracts. The orange peel (Op) and pomegranate peel (Pp) exhibit a high antioxidant potential. The ethno pharmacological utilization of the fruit and their peel extracts is prevalent in a variety of cultures to cure common disorders without any consideration of its phytochemical profile with there toxicological limit. The phenolic compounds possess different biological activities, but most of the important one are their antioxidant activities. The main aim of this study was evaluation of the bioactive components in orange and pomegranate peel. Specific objectives of this study were extraction and characterisation of the orange and pomegranate peel in terms of yield. Estimation of total cellulose content, estimation oftotalotal phenolic content, estimation of total tannin and evaluation of the effects of heat treatment on physicochemical properties and bioactive compounds of fresh orange and pomegranate peel.